Movimentos de uma juventude bailarina: estigma, sexualidade e formação na Escola de Dança de Paracuru - Campos, Marcos Antônio Almeida (2018)
This work aims at persecuting the narratives of young people about their training as dancers performed at the Escola de Dança de Paracuru (Paracuru Dance School) and the stigmas faced by men who dance ballet. The main theoretical categories of reference were: stigma, homophobia, insult, youth, gender and sexuality. This is a qualitative research, based on the ethnographic approach, performed at the Escola de Dança de Paracuru in the state of Ceará. The fieldwork was carried out for thirteen months, through participant observation, field journal, individual interviews, with the direct collaboration of eight subjects and indirectly from the entire team of the Escola de Dança de Paracuru. The research results point out the challenges faced by both male and female dancers regarding the acceptance and denial of their families and of the city of Paracuru concerning the dance as a work perspective, in addition to the stigmas and prejudices suffered from the matters of sexuality referred to the practice of ballet, mainly by boys. The narratives indicate that, slowly, the aggressions and the discredit of the population were attenuated, in a process of de-stigmatization of practices and training in dance. Nowadays, the Escola de Dança de Paracuru has a model status in the town and has become a pride and a reference in the youth development.